Permanence of Employees in Family Businesses: What Matters from the Perspective of Managers? - Meurer, Tatiane (2023)
This paper explores what is important for the permanence of non-family employees in family businesses, from the perspective of family and non-family managers. Qualitative research was conducted, guided by semi-structured interviews with 11 interviewees, including non-family employees and business family members. Content analysis was performed using MaxQDA software, followed by a code book and intercoder reliability test using the R language. The results revealed five categories concerning the reasons for the permanence of employees in the investigated family businesses: i) flexible communication, ii) career opportunity, iii) humanized work, iv) sense of belonging, and v) regional setting. Furthermore, there is an indication that the sense of belonging is driven by the first three listed categories, influencing the non-family employee's willingness to stay in the organization. Based on the findings, the paper presents propositions to be investigated in future research. As practical implications, training and qualifications that encourage flexible communication, career opportunities, humanized work, and a sense of belonging are suggested to strengthen the permanence of non-family employees.